The effects of foliar fertilization with iron sulfate in chlorotic leaves are limited to the treated area. A study with peach trees (Prunus persica L. Batsch) grown in the field and sugar beet (Beta vulgaris L.) grown in hydroponics - El-Jendoubi, Hamdi; Vázquez, Saúl; Calatayud, Ángeles; Vavpetič, Primož; Vogel-Mikuš, Katarina; Pelicon, Primoz; Abadía, Javier; Abadía, Anunciación; Morales, Fermín (Frontiers in Plant Science, 2014)
Crop Fe deficiency is a worldwide problem. The aim of this study was to assess the effects of foliar Fe applications in two species grown in different environments: peach (Prunus persica L. Batsch) trees grown in the field and sugar beet (Beta vulgaris L. cv. ‘Orbis’) grown in hydroponics. The distal half of Fe-deficient, chlorotic leaves was treated with Fe sulfate by dipping and using a brush in peach trees and sugar beet plants, respectively. The re-greening of the distal (Fe-treated) and basal (untreated) leaf areas was monitored, and the nutrient and photosynthetic pigment composition of the two areas were also determined. Leaves were also studied using chlorophyll fluorescence imaging, low temperature-scanning electron microscopy microanalysis, scanning transmission ion microscopy-particle induced X-ray emission and Perls Fe staining. The distal, Fe-treated leaf parts of both species showed a significant increase in Fe concentrations (across the whole leaf volume) and marked re-greening, with significant increases in the concentrations of all photosynthetic pigments, as well as decreases in de-epoxidation of xanthophyll cycle carotenoids and increases in photochemical efficiency. In the basal, untreated leaf parts, Fe concentrations increased slightly, but little re-greening occurred. No changes in the concentrations of other nutrients were found. Foliar Fe fertilization was effective in re-greening treated leaf areas both in peach trees and sugar beet plants. Results indicate that the effects of foliar Fe-sulfate fertilization in Fe-deficient, chlorotic leaves were minor outside the leaf surface treated, indicating that Fe mobility within the leaf is a major constraint for full fertilizer effectiveness in crops where Fe-deficiency is established and leaf chlorosis occurs.